2017
DOI: 10.1093/biolre/iox110
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose metronomic delivery of cyclophosphamide is less detrimental to granulosa cell viability, ovarian function, and fertility than maximum tolerated dose delivery in the mouse†

Abstract: Chemotherapy can cause early menopause or infertility in women and have a profound negative impact on the quality of life of young female cancer survivors. Various factors are known to influence the risk of chemotherapy-induced ovarian failure, including the drug dose and treatment duration; however, the scheduling of dose administration has not yet been evaluated as an independent risk factor. We hypothesized that low-dose metronomic (LDM) chemotherapy scheduling would be less detrimental to ovarian function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…And the results showed that the rhLF treatments significantly protected the primary rat GCs from the 4-HC treatments via the inhibition of ROS production and the promotion of cellular proliferation, which was consistent with the in vivo results of rhLF administrations. In addition, the high expression levels of Bax after 4-HC treatments revealed the increased levels of cellular apoptosis, which was consistent with these previous studies about the exposure to chemotherapy drugs in vitro and high levels of GCs apoptosis [5,14,55,82], and our results further confirmed the main target of rhLF treatments during POF was GCs. However, due to the complex in vivo microenvironments including oocytes and follicular cells (GCs, theca cells and stroma cells) in mammalian ovaries, the ameliorative target of rhLF on the POF damages needs more detailed in vitro investigations.…”
Section: Discussionsupporting
confidence: 92%
“…And the results showed that the rhLF treatments significantly protected the primary rat GCs from the 4-HC treatments via the inhibition of ROS production and the promotion of cellular proliferation, which was consistent with the in vivo results of rhLF administrations. In addition, the high expression levels of Bax after 4-HC treatments revealed the increased levels of cellular apoptosis, which was consistent with these previous studies about the exposure to chemotherapy drugs in vitro and high levels of GCs apoptosis [5,14,55,82], and our results further confirmed the main target of rhLF treatments during POF was GCs. However, due to the complex in vivo microenvironments including oocytes and follicular cells (GCs, theca cells and stroma cells) in mammalian ovaries, the ameliorative target of rhLF on the POF damages needs more detailed in vitro investigations.…”
Section: Discussionsupporting
confidence: 92%
“…In a study conducted by Dynes et al [ 36 ], it was demonstrated that metronomic chemotherapy using a dosage of 20 mg/kg/day CTX in mice was effective. Therefore, for this study, metronomic chemotherapy was administered to mice with a CTX dose of 20 mg/kg/day.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the effect of Cy on activation of cellular senescence, GLCs were treated with an active metabolite of Cy, 4-HC [32,33] (Toronto Research Chemicals, Toronto, ON, Canada), at concentrations of 0.001-100 µM for 24 h. These conditions were chosen based on previous studies that used human cells or animal GLCs [34][35][36]. Treatment with 10 µM 4-HC for 24 h exerted the maximum effect without changing cellular morphology.…”
Section: Treatment Of Human Glcsmentioning
confidence: 99%